Workshop Pengembangan Media Pembelajaran Matematika berbasis GeoGebra dan Augmented Reality - Harry Soeprianto; Muhammad Turmuzi; Junaidi Junaidi; Ulfa Lu'luilmaknun (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
the engagement activity begins with the development of technology and communication, as well as the high demand for mathematics learning media by teachers. On the other hand, the quality of education, particularly in junior high schools, is still low. Teachers' competence, especially in media usage and development, is also low. Therefore, a workshop on media development will be conducted to enhance teachers' competence and the availability of learning media. The implementation methods for this engagement activity include material presentations, demonstrations, practical exercises, group discussions, and evaluation with feedback. The results of this engagement activity show that the majority of junior high school teachers in Central Lombok believe that the use of Geogebra and augmented reality in mathematics learning has the potential to improve students' understanding of concepts, interest, motivation, creativity, and learning outcomes. Teachers also acknowledge the importance of their role in effectively integrating this technology. Thus, the use of Geogebra and augmented reality-based learning media can provide positive benefits in enhancing the quality of mathematics education in schools. It is important to consider contextual factors and readiness when implementing Geogebra and augmented reality. The utilization of technology, especially Geogebra and augmented reality, should be tailored to the needs, availability of resources, and characteristics of each educational level.